A new species of Chusquea (Poaceae: Bambusoideae: Bambuseae) in the C. meyeriana informal group from southeastern Brazil - Clark, Lynn G.; Vidal, Kaio Vinicius de A.; Oliveira, Reyjane P.; Leandro, Thales D. [UNESP] (Springer Nature, 2022)
The Chusquea meyeriana informal group within Chusquea subg. Chusquea is endemic to the Atlantic forests of southeastern Brazil and includes seven described species (C. anelythra, C. anelytroides, C. attenuata, C. clemirae, C. longispiculata, C. meyeriana and C. parviligulata). Work on the treatment of Chusquea for the Flora do Brasil allowed us to confirm the presence of another unnamed species belonging to this group, which we here describe as Chusquea cordata. We compared its morphology with that of the partially sympatric C. longispiculata. Chusquea cordata is distinguished based on its cordate culm leaf blades, unique within this informal group, and smaller synflorescences and spikelets than in C. longispiculata, among other characters. In addition to line illustrations of the new species, a map of its geographical distribution and a key to the species of the C. meyeriana informal group based on vegetative characters, we illustrate the foliar micromorphology and anatomy of C. cordata and C. longispiculata to highlight both similarities and differences. Because the C. meyeriana informal group has been defined by differing combinations of vegetative and reproductive characters by various authors, we propose an updated combination of diagnostic features including a new character. This informal group is now diagnosed by: the presence of a white waxy infranodal band; culm leaves with at least a slight corky ridge at the juncture of the girdle and sheath; at least initially infravaginal branching; synflorescences subtended by 1–4 spatheate bracts; the lower two primary synflorescence branches strongly reflexed; and spikelets with very reduced glumes I and II. With this new species, Chusquea comprises 198 described species, of which 49 occur in Brazil, with 45 of them endemic.
Keywords: Atlantic forest; Chusquea cordata; Chusquea longispiculata; Chusqueinae; Leaf anatomy; Leaf micromorphology